FREEDOM OF EXPRESSION OF LAWYERS THROUGH THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Đukić, Dimitrije (Glasnik Advokatske komore Vojvodine, 2021)
Freedom of expression is an important freedom that has had a great impact on menkind and the protection of this freedom is provided by numerous domestic and international legal instruments. This paper analyzes how the freedom of expression of a special group of persons - lawyers is protected through the practice of the European Court of Human Rights. The author’s view is that lawyers, because of their importance in society, must enjoy greater freedom of expression than other groups and that the restriction of this freedom should be approached restrictively. In this respect, the paper will firstly analyze the role and function that lawyers have in society. It will then analyze how freedom of expression is protected by the European Convention on Human Rights and in the case-law of the European Court of Human Rights. Finally, special emphasis is given on the possibility of restricting this freedom and analyzing the positions taken by the European Court of Human Rights in this regard.